URGENSI ALTERNATIF PENYELESAIAN SENGKETA MELALUI MEDIASI DALAM PENYELESAIAN SENGKETA KESEHATAN - Siregar, Abdul Rahman Maulana; Sidi, Redyanto; Fikri, Rahul Ardian; Theresa, Elbina (Universitas Negeri Medan, 2024)
This paper aims to discuss the importance of alternative dispute resolution in resolving health disputes through mediation as stated in Law Number 17 of 2023 concerning Health. Health disputes involve conflicts between patients and medical personnel, health workers or hospitals. This paper will discuss the urgency of alternative dispute resolution through mediation in resolving health disputes after the enactment of Law Number 17 of 2023 concerning Health. The results of this paper can provide benefits on how important it is to resolve health disputes through mediation without going through the role of the courts which are expected to create a win-win solution for all parties.